Learning Application of Multimedia-Based-Computer Network Using Computer Assisted Instruction Method - Simarmata, Janner; Limbong, Tonni; Napitupulu, Efendi; Sriadhi, S; R S Tambunan, A; Keristiana Sinaga, Enny; ., Suhairiani; G G T Sibarani, C; Arafat Lubis, Maulana; Irwan Padli Nasution, Muhammad; Purnomo, Agung; Anam, Fatkul; et al. (International Journal of Engineering and Technology, 2018)
In conventional learning, teachers frequently face difficulties to deliver their materials due to limited time and practical materials in teaching network computer. Conventional teaching process, especially practical materials, has still not yet been optimal. Thus, computer and multimedia based learning is required to help the students. Besides it can reduce costs in practical materials procurement, the students can absorb the given knowledge well without thinking of the costs to buy the practical materials. Computer Assisted Instruction Method can present the learning using various media either by picture or video that can assist the effective learning process and simplify the students to manage the learning speed since it is combined with the multimedia. By doing this, the students can practice the lesson materials, study whenever and wherever they want. Compuer learning application prioritize user interface, user friendly, which can make the students be diligent and passionate in learning.Â